Definition and classification of rockburst - Manchao He; Ismet Canbulat; Fidelis T. Suorineni; Murat Karakus; Wen Nie; Dongqiao Liu; Chengguo Zhang; Alexey Nagibin; Bauyrzhan Rustembek (Rock Mechanics Bulletin, 2025)
The rockburst is a violent failure in rock during mining and tunneling operations. Since tunnel constructions for hydropower and transportation purposes and mining operations in deep rock masses have been increasing recently, more frequent rockburst cases have been reported. This paper proposes a new definition for rockburst, considering the main components of the rockburst along with triggering mechanisms and reasons. For this purpose, the historical definitions of rockburst and its related classifications have been reviewed. In terms of triggering mechanisms, a rockburst must be induced by excavation resulting from three effects arising from the transition of stress state from 3- to 1-dimension, such as the transient radial stress loss, the time-dependent tangential stress increase, and the peak strength drop, which are explained by examining the stress transition in the shear stress vs normal stress space and energy transition in the stress-strain space. Based on the understanding of the three effects of excavation, a new definition of rockburst is proposed: “A rockburst is a sudden failure of rock mass surrounding the excavations caused by the rapid release of stored energy when induced stresses exceed the rock strength”. Additionally, rockbursts are classified according to transitions in the static and dynamic stress fields, with further subclassifications into instantaneous and delayed bursts based on the timing of occurrences relative to radial stress drop and tangential stress increase. Rockburst management strategies are also proposed to address stress and energy transitions in excavations.